2020
DOI: 10.1111/btp.12842
|View full text |Cite
|
Sign up to set email alerts
|

Chemical defenses shift with the seasonal vertical migration of a Panamanian poison frog

Abstract: Dendrobatid poison frogs sequester lipophilic alkaloids from their arthropod prey to use as a form of chemical defense. Some dendrobatid frogs seasonally migrate between the leaf litter of the forest floor in the dry season to the canopy in the wet season, which may yield differences in prey (arthropods) and therefore alkaloid availability over space and time. Here, we document a seasonal vertical migration of Andinobates fulguritus (the yellow‐bellied poison frog) from ground to canopy between dry and wet sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…from the upper part during the dry months. This behavior has been documented in other species of tree frogs, such as adults of Agallychnis spurrelly (Ortega-Andrade et al, 2011), and a decrease in reproductive activity and number of individuals found near bodies of water during the dry season have been reported (Muñoz-Guerrero et al, 2007;Touchon & Warkentin, 2009), so it is to be expected that these individuals migrate towards the forest canopy when the rainy season has ended, and like many other frogs, their activity stimulated by rain (Donnelly & Guyer 1994;Vasconcelos, 2010), contrary to the vertical migrations observed in some species of frogs of the Dendrobatidae family, which migrate from the forest floor to the tree canopy during the rainy season (Basham et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…from the upper part during the dry months. This behavior has been documented in other species of tree frogs, such as adults of Agallychnis spurrelly (Ortega-Andrade et al, 2011), and a decrease in reproductive activity and number of individuals found near bodies of water during the dry season have been reported (Muñoz-Guerrero et al, 2007;Touchon & Warkentin, 2009), so it is to be expected that these individuals migrate towards the forest canopy when the rainy season has ended, and like many other frogs, their activity stimulated by rain (Donnelly & Guyer 1994;Vasconcelos, 2010), contrary to the vertical migrations observed in some species of frogs of the Dendrobatidae family, which migrate from the forest floor to the tree canopy during the rainy season (Basham et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in addition to previously known factors-including geographic location (Saporito et al, 2006;Saporito et al, 2007), season (Basham et al, 2020;Saporito et al, 2006), and age and life stage (Daly et al, 2002;Stynoski et al, 2014)variation in accumulation efficiency in relation to both the type and amount of alkaloid also contributes causally to the high variation in alkaloid composition among poison frog individuals and species. We also raise the possibility that differences in alkaloid lipophilicity might affect sequestration efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these ndings suggest that the abundance of biosynthesized pseudophrynamines are dependent on the availability of dietary alkaloids. Variation in dietary alkaloids is common among poison frogs and is thought largely to result from spatial and temporal differences in arthropods (Saporito et al 2007a;McGugan et al 2016;Moskowitz et al 2020;Basham et al 2021). It is therefore plausible that changes in availability of dietary alkaloids could lead to differences in the production of pseudophrynamines, something that would be expected to change over the course of a lifetime.…”
Section: Discussionmentioning
confidence: 99%